Positive electrode composite material, preparation method thereof and sodium ion battery
By covering a mixed layer of mixed phosphate and carbon source on the surface of the positive electrode material matrix, the problem that the positive electrode material coating in the prior art cannot have excellent electron and ion conductivity, which significantly improves the electrochemical performance of sodium ion batteries.
Patent Information
- Application Number
- CN202411682987.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-08
AI Technical Summary
The existing positive electrode material cladding cannot have excellent electronic conductivity and ionic conductivity, and cannot adapt under high voltage conditions, resulting in rapid capacity attenuation and reduced operating voltage.
A cladding layer consisting of a mixed phosphate and a carbon source is induced to uniformly coat the conductive carbon and phosphate on the surface of the matrix of the positive electrode material by sol-gel method and dispersant.
It significantly improves the electrochemical performance of sodium ion batteries, including improving the ion/electronic conductivity of the material, enhancing the circulation and rate performance, protecting the positive electrode material, reducing side reactions, and preventing the occurrence of surface cracks.
Smart Images

Figure CN119786552A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and in particular relates to a positive electrode composite material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the increasing demand for large-scale energy storage, the demand for lithium-ion batteries is also increasing. However, due to the limited natural abundance and uneven distribution of lithium (Li) on the earth (mainly concentrated in South America), people have begun to pay attention to the sustainability of lithium-ion batteries. In addition, lithium-ion batteries also face challenges in safety and low-temperature performance. Therefore, there is an urgent need to explore low-cost, high-natural abundance and excellent performance rechargeable battery systems to prepare for the next generation of energy storage applications. my country is rich in sodium resources (accounting for 22% of the world's reserves), and its reserves are much higher than lithium resources (accounting for 6% of the world's reserves). Compared with other metal-ion batteries, sodium-ion batteries have a relatively low cost, excellent adaptability to various environmental conditions, and significant advantages in low temperature and fast charging performance. Therefore, sodium-ion batteries are regarded as one of the main competitors for the next generation of energy storage applications.
[0003] The O3-type positive electrode layered oxide material for sodium ion batteries has the advantages of high capacity and easy synthesis, but it will undergo surface side reactions with the electrolyte under high voltage conditions, causing lattice oxygen loss, resulting in rapid capacity decay and reduced operating voltage. In addition, O3-type materials with higher sodium content have stronger air sensitivity. During storage, water molecules in the air accelerate the dissolution of Na+ from the lattice through Na / H+ exchange, and eventually react with carbon dioxide in the air to form carbonates, resulting in gelation in the coating process and decreased electrochemical performance. To solve the above problems, the positive electrode material is usually protected by providing a coating layer on the surface of the layered oxide positive electrode material. The existing coating layer is usually an oxide or a phosphate. However, the oxide coating layer is a poor conductor of sodium ions, which will hinder the migration of sodium ions and increase the impedance of the electrochemical process, while the phosphate coating layer has poor electronic conductivity, which will hinder electron transmission and reduce the kinetic properties of the material.
[0004] Therefore, developing a positive electrode material with an ideal coating effect, excellent electronic conductivity and ionic conductivity, and the ability to adapt to high-voltage working environments is of great significance for the development of high-energy-density sodium-ion batteries. Summary of the invention
[0005] The purpose of the embodiments of the present application is to provide a method for solving the problem that the existing positive electrode material coating layer cannot have both excellent electronic conductivity and ionic conductivity and cannot adapt to high voltage working environment.
[0006] The embodiment of the present application is implemented as follows: a positive electrode composite material, the positive electrode composite material includes a positive electrode material matrix and a coating layer coated on the surface of the positive electrode material matrix, and the coating layer is composed of a mixed phosphate and a carbon source.
[0007] Preferably, the mixed phosphate is M x PO4, M x One or more of P2O7, HPO3, H3PO4, NH4H2PO4, wherein M includes one or two of Sb, Sc, Y, La, Ce, Sm, Gd, Dy, and Ta; and the carbon source is one or two of glucose, citric acid, ascorbic acid, carbon nanotubes, and graphene.
[0008] Preferably, the chemical formula of the positive electrode composite material is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#MPO4@C, wherein M includes at least one of Sb, Sc, Y, La, Ce, Sm, Gd, Dy, and Ta; and C is one or two of glucose, citric acid, ascorbic acid, carbon nanotubes, and graphene.
[0009] Preferably, in the coating layer, the mass of the carbon source accounts for 1-10wt% of the mass of the positive electrode material matrix, and the mass of the mixed phosphate accounts for 0.3-3wt% of the mass of the positive electrode material matrix; the thickness of the coating layer is 1-15nm.
[0010] The present application also provides a method for preparing the above-mentioned positive electrode composite material, comprising:
[0011] The cathode material matrix is added into the modified solution of the mixed phosphate and the carbon source to be evenly dispersed, stirred and heated to vaporize the solvent, and dried to obtain a cathode material precursor powder of the mixed coating layer;
[0012] The mixed coating layer positive electrode material precursor powder is tableted and sintered to obtain a positive electrode composite material.
[0013] Preferably, the modified solution of mixed phosphate and carbon source comprises phosphate, carbon source, dispersant and organic solvent; wherein the dispersant comprises one or more of polyethylene, polypropylene, polystyrene, sodium polyacrylate and polyvinyl alcohol; and the organic solvent comprises one or more of ethanol, ethylene glycol, ether and isopropyl ketone.
[0014] Preferably, in the modified solution of the mixed phosphate and carbon source, the mass fraction of the phosphate is 0.3-3wt%, the mass fraction of the carbon source is 1-10wt%, and the mass fraction of the dispersant is 0.1-0.3wt%.
[0015] An embodiment of the present application also provides a sodium ion battery, which includes the above-mentioned positive electrode composite material.
[0016] The surface of the positive electrode composite material provided in the embodiment of the present application is coated with a mixed coating layer of a high-valent metal phosphate and a carbon layer. The conductive carbon and the high-valent metal phosphate in the mixed layer have a synergistic effect, which can improve the ion / electronic conductivity of the material and enhance the electrochemical properties such as cycle and rate. In addition, in the coating layer of the positive electrode composite material, the conductive carbon not only has the advantage of high electronic conductivity, but also can form a mixed coating structure with phosphates with high ionic conductivity, and avoids the positive electrode material matrix from being soaked in solution, resulting in a decrease in capacity, and the capacity can be restored by secondary sintering after coating; at the same time, the phosphate has a wide sodium ion diffusion channel to ensure the high electronic conductivity and lithium ion conductivity of the mixed coating layer, and the internal electron and ion transmission of the material is fast, and the electrochemical rate performance is good. In addition, the coating layer can protect the positive electrode material, reduce side reactions during the electrochemical reaction, and prevent the generation of surface cracks. This application successfully provides an efficient transmission channel for electrons and ions on the surface of the positive electrode material matrix by coating phosphate and conductive carbon on the positive electrode material matrix, which can significantly improve the electrochemical performance of sodium ion batteries.
[0017] The preparation method of the positive electrode composite material provided in the embodiment of the present application successfully uniformly coats a mixed coating layer of conductive carbon and phosphate on the surface of the positive electrode material matrix through the sol-gel method and dispersant induction. The high-valent metal phosphate has a wide sodium ion diffusion channel, which can promote the diffusion of sodium ions and regulate the flow of electrons, further protect the positive electrode material matrix, and stabilize the performance of the high-voltage sodium ion battery. In addition, the preparation method of the present application is a wet coating method, and the coating process does not require high temperature, and has little effect on the positive electrode material matrix. The process is simple and the process is short. It can be incorporated into the existing technology production line, which is convenient for large-scale system operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the positive electrode composite material provided in Example 1 of the present application;
[0019] Figure 2 This is a SEM image of the positive electrode composite material provided in Comparative Example 1 of the present application;
[0020] Figure 3 This is a SEM image of the positive electrode composite material provided in Comparative Example 3 of the present application;
[0021] Figure 4 1C cycle performance diagram of the positive electrode composite material provided in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present application;
[0022] Figure 51C cycle performance diagram of the positive electrode composite material provided in Example 1, Examples 7-9, and Comparative Examples 4-6 of the present application;
[0023] Figure 6 This is a TEM image of the positive electrode composite material provided in Example 1 of the present application. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0025] An embodiment of the present application provides a positive electrode composite material, which includes a positive electrode material matrix and a coating layer coated on the surface of the positive electrode material matrix, wherein the coating layer is composed of a mixed phosphate and a carbon source.
[0026] In an embodiment of the present application, the positive electrode material matrix may be immersed in a modified solution in which phosphate and carbon source are uniformly mixed, and then subjected to high-temperature sintering to obtain the positive electrode composite material.
[0027] In a preferred embodiment of the present application, the mixed phosphate is a pyrophosphate (phosphoric acid) salt containing a high-valent metal ion. Phosphate is an excellent sodium ion conductor; high-valent metal ions can stabilize surface lattice oxygen, regulate charge transfer, and improve electronic conductivity. Preferably, the mixed phosphate is M x PO4, M x One or more of P2O7, HPO3, H3PO4, NH4H2PO4, wherein M includes one or two of Sb, Sc, Y, La, Ce, Sm, Gd, Dy, and Ta. The preferred high-valent metal has a unique electronic structure and can significantly improve the electrochemical performance of the positive electrode material under high voltage.
[0028] In the preferred embodiment of the present application, the requirements for the carbon source are that it has high electronic conductivity, has more voids, and is easy to form a mixed coating layer with phosphate, preferably one or two of glucose, citric acid, ascorbic acid, carbon nanotubes, and graphene. The preferred carbon source can ensure that the capacity of the positive electrode material does not decrease after being immersed.
[0029] In an optional embodiment of the present application, the cathode material matrix is an O3 phase sodium ion layered oxide, and the chemical formula of the cathode composite material is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2#MPO4@C, wherein M includes at least one of Sb, Sc, Y, La, Ce, Sm, Gd, Dy, and Ta. It should be noted that although the specific embodiments and comparative examples of the present application are described with the cathode material matrix being a nickel-iron-manganese-based material as an example, those skilled in the art should understand that other O3-type nickel-manganese-based, iron-manganese-based, nickel-iron-copper-manganese-based, etc. are all applicable to the modification method of the present application.
[0030] In an optional embodiment of the present application, in the coating layer, the mass of the carbon source accounts for 1-10wt% of the mass of the positive electrode material matrix, for example, it can be 1wt%, 2wt%, 3wt%, 5wt%, 6wt%, 8wt% or 10wt%, etc.; the mass of the mixed phosphate accounts for 0.3-3wt% of the mass of the positive electrode material matrix, for example, it can be 0.3wt%, 0.5wt%, 1wt%, 2wt% or 3wt%, etc.
[0031] In a preferred embodiment of the present application, the thickness of the coating layer is controlled to be 1nm-15nm. Controlling the appropriate coating layer thickness can increase the stability and conductivity of the positive electrode material without affecting the capacity of the positive electrode material. The thickness of the coating layer can be obtained by FIB-TEM (Focused Ion Beam-Transmission Electron Microscope) testing. In some embodiments, the thickness of the coating layer can be, for example, 1nm, 2nm, 5nm, 8nm, 9nm, 10nm or 15nm. In an embodiment of the present application, the coating layer can cover part or all of the surface of the kernel, and the morphology of the coating layer can be a film, a granular, or a mixed morphology of a film and a granular.
[0032] The present application also provides a method for preparing the above-mentioned positive electrode composite material, comprising:
[0033] The cathode material matrix is added into the modified solution of the mixed phosphate and the carbon source to be evenly dispersed, stirred and heated to vaporize the solvent, and dried to obtain a cathode material precursor powder of the mixed coating layer;
[0034] The mixed coating layer positive electrode material precursor powder is tableted and sintered to obtain a positive electrode composite material.
[0035] In the embodiment of the present application, the modified solution of mixed phosphate and carbon source includes phosphate, carbon source, dispersant and organic solvent; the modified solution of mixed phosphate and carbon source can be obtained by conventionally mixing the components. The dispersant includes one or more of polyethylene, polypropylene, polystyrene, sodium polyacrylate, and polyvinyl alcohol; the organic solvent includes one or more of ethanol, ethylene glycol, ether, and isopropyl ketone.
[0036] It is worth noting that the dispersant used in this application has a low boiling point and can be easily removed during the subsequent sintering process. At the same time, the dispersant does not show visible degradation in the sodium ion battery electrolyte, which can improve the performance of the resulting electrode. In addition, this application coats the ionic electronic conductor on the collective surface of the positive electrode material, and introduces a dispersant to induce the tight coating of the conductive carbon, which effectively enhances the electronic conductivity of the positive electrode material and can be adapted to the positive electrode material matrix working at high voltage.
[0037] In an embodiment of the present application, in the modified solution of the mixed phosphate and carbon source, the mass fraction of the phosphate is 0.3-3wt%, the mass fraction of the carbon source is 1-10wt%, and the mass fraction of the dispersant is 0.1-0.3wt%.
[0038] In an optional embodiment of the present application, the step of adding the cathode material matrix to the modified solution of the mixed phosphate and the carbon source to disperse uniformly, stirring and heating to vaporize the solvent, and drying to obtain a mixed coating layer cathode material precursor powder includes:
[0039] The cathode material matrix is added to the modified solution of the mixed phosphate and carbon source and dispersed evenly, heated and stirred at a temperature of 80-110°C for 5-8 hours to vaporize the solvent, and then placed at a temperature of 80-120°C for drying for 6-10 hours to obtain a mixed coating layer cathode material precursor powder. Among them, the present application heats to volatilize the solvent, which solves the problem of uneven coating in the traditional solid phase method; the preferred carbon source can avoid the problem of reduced capacity caused by the cathode material matrix being immersed in the solution after sintering.
[0040] In an optional embodiment of the present application, the pressure applied during tableting is 5-50 MPa, preferably 10-20 MPa.
[0041] In an optional embodiment of the present application, the step of tableting the mixed coating layer positive electrode material precursor powder and sintering it to obtain a positive electrode composite material comprises:
[0042] The mixed coating layer cathode material precursor powder is tableted, placed in an inert gas or oxygen atmosphere, heated to 450-850°C at a heating rate of 2-5°C / min, and kept warm for 5-12 hours to obtain a cathode composite material. The inert gas can be any one of argon, nitrogen, and helium.
[0043] The following specific examples are used to describe the positive electrode composite material and its preparation method and application in detail, as shown below. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0044] Embodiment 1:
[0045] In this embodiment, the positive electrode composite material includes a positive electrode material matrix NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and a mixed coating layer of multi-walled carbon nanotubes and lanthanum phosphate coated on the surface of the positive electrode material matrix, the mass of the multi-walled carbon nanotubes in the mixed coating layer accounts for 5wt% of the mass of the positive electrode material, and the mass of the phosphate accounts for 0.5wt% of the mass of the positive electrode material.
[0046] The method for preparing the positive electrode composite material comprises the following steps:
[0047] (1) 0.3 wt% LaPO4 was uniformly dispersed in a 5 wt% multi-walled carbon nanotube solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 minutes to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is ethylene glycol, which contains 0.2 wt% LDS, and the average length of the multi-walled carbon nanotubes is 5 μm and the average outer diameter is 12 nm.
[0048] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@LaPO4.
[0049] Embodiment 2:
[0050] In this embodiment, the positive electrode composite material includes a positive electrode material matrix NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and a mixed coating layer of graphene and cerium phosphate coated on the surface of the positive electrode material matrix, the mass of graphene in the mixed coating layer accounts for 10wt% of the mass of the positive electrode material, and the mass of cerium phosphate accounts for 1wt% of the mass of the positive electrode material.
[0051] The method for preparing the positive electrode composite material comprises the following steps:
[0052] (1) 1 wt% CePO4 was uniformly dispersed in a graphene solution with a mass content of 10 wt%, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was dispersed in the modified solution, and stirred at 400 rpm and 110°C for 60 min to vaporize the solvent to obtain a positive electrode composite material precursor powder, wherein the solvent in the graphene solution was ethanol, which contained 0.2 wt% LDS.
[0053] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 15 MPa, and then the disc is placed in a box furnace with an air atmosphere, and the temperature is increased to 650° C. at a heating rate of 3° C. / min, and the temperature is kept for 10 hours, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#GO@CePO4.
[0054] Embodiment 3:
[0055] In this embodiment, the positive electrode composite material includes a positive electrode material matrix NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and a mixed coating layer of glucose and gadolinium phosphate coated on the surface of the positive electrode material matrix, the mass of glucose in the mixed coating layer accounts for 5wt% of the mass of the positive electrode material, and the mass of gadolinium phosphate accounts for 0.3wt% of the mass of the positive electrode material.
[0056] The method for preparing the positive electrode composite material comprises the following steps:
[0057] (1) 0.3 wt% GdPO4 was uniformly dispersed in a 5 wt% glucose solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 min to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the glucose solution was ethylene glycol.
[0058] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 20 MPa, and then the disc is placed in a box furnace with an argon atmosphere, and the temperature is increased to 550° C. at a heating rate of 3° C. / min, kept for 12 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#C@GdPO4.
[0059] Embodiment 4:
[0060] The difference between this embodiment and embodiment 1 is that compared with step (1), 0.3 wt% NH4H2PO4 is additionally added, and the other processes and conditions are the same as those in embodiment 1 to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@Na4La(PO4)P2O 7。
[0061] Embodiment 5:
[0062] In this embodiment, the positive electrode composite material includes a positive electrode material matrix NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and a mixed coating layer of multi-walled carbon nanotubes and gadolinium phosphate coated on the surface of the positive electrode material matrix, the mass of the multi-walled carbon nanotubes in the mixed coating layer accounts for 5wt% of the mass of the positive electrode material, and the mass of the phosphate accounts for 0.5wt% of the mass of the positive electrode material.
[0063] The method for preparing the positive electrode composite material comprises the following steps:
[0064] (1) 0.3 wt% GdPO4 was uniformly dispersed in a 5 wt% multi-walled carbon nanotube solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 minutes to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is ether containing 0.2 wt% LDS, and the average length of the multi-walled carbon nanotubes is 5 μm and the average outer diameter is 12 nm.
[0065] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@LaPO4.
[0066] Embodiment 6:
[0067] In this embodiment, the positive electrode composite material includes a positive electrode material matrix NaNi1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and a mixed coating layer of multi-walled carbon nanotubes and samarium phosphate coated on the surface of the positive electrode material matrix, the mass of the multi-walled carbon nanotubes in the mixed coating layer accounts for 5wt% of the mass of the positive electrode material, and the mass of the phosphate accounts for 0.5wt% of the mass of the positive electrode material.
[0068] The method for preparing the positive electrode composite material comprises the following steps:
[0069] (1) 0.3 wt% SmPO4 was uniformly dispersed in a 5 wt% multi-walled carbon nanotube solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 minutes to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is ethylene glycol, which contains 0.2 wt% LDS, and the average length of the multi-walled carbon nanotubes is 5 μm and the average outer diameter is 12 nm.
[0070] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@SmPO4.
[0071] Embodiment 7:
[0072] This embodiment is a positive electrode material coated with lanthanum phosphate and citric acid. The mass content of lanthanum phosphate is 0.3wt% relative to the positive electrode material. The preparation method is as follows:
[0073] (1) 0.3 wt% LaPO4 was uniformly dispersed in a 5 wt% citric acid solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was dispersed in the modified solution at 400 rpm.
[0074] The mixture was stirred at 110° C. for 60 minutes to vaporize the solvent, thereby obtaining a positive electrode composite material precursor powder, wherein the solvent in the citric acid solution was ethylene glycol, which contained 0.2 wt % LDS.
[0075] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#C@
[0076] LaPO4.
[0077] Embodiment 8:
[0078] This embodiment is a positive electrode material coated with lanthanum phosphate and multi-walled carbon nanotubes. The mass content of lanthanum phosphate is 2wt% relative to the positive electrode material. The preparation method is as follows:
[0079] (1) 2 wt% LaPO4 was uniformly dispersed in a 5 wt% multi-walled carbon nanotube solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 minutes to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is ethylene glycol, which contains 0.2 wt% LDS, and the average length of the multi-walled carbon nanotubes is 5 μm and the average outer diameter is 12 nm.
[0080] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@LaPO4.
[0081] Embodiment 9:
[0082] This embodiment is a positive electrode material coated with lanthanum phosphate and multi-walled carbon nanotubes. The mass content of lanthanum phosphate is 3wt% relative to the positive electrode material. The preparation method is as follows:
[0083] (1) 3 wt% LaPO4 was uniformly dispersed in a 5 wt% multi-walled carbon nanotube solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 O2 is dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 minutes to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is ethylene glycol, which contains 0.2 wt% LDS, and the average length of the multi-walled carbon nanotubes is 5 μm and the average outer diameter is 12 nm.
[0084] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@LaPO4.
[0085] Comparative Example 1:
[0086] This comparative example directly uses the nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is used as the positive electrode material.
[0087] Comparative Example 2:
[0088] This comparative example is a multi-walled carbon nanotube coated positive electrode material. Relative to the positive electrode material, the mass content of the multi-walled carbon nanotube is 5wt%, and the preparation method is:
[0089] (1) 5g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is dispersed in a multi-walled carbon nanotube solution with a mass content of 5wt%, and stirred at 400rpm and 110°C for 60min to vaporize the solvent to obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is ethylene glycol, which contains 0.2wt% LDS, and the average length of the multi-walled carbon nanotubes is 5μm and the average outer diameter is 12nm.
[0090] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn1 / 3 O2#CNT.
[0091] Comparative Example 3:
[0092] This comparative example is a lanthanum phosphate coated positive electrode material. The mass content of lanthanum phosphate is 0.5wt% relative to the positive electrode material. The preparation method is:
[0093] (1) 5g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is dispersed in a LaPO4 solution with a mass content of 0.5wt%, and stirred at 400rpm and 110°C for 60min to vaporize the solvent to obtain a positive electrode composite material precursor powder. The solution is ethylene glycol.
[0094] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2@LaPO4.
[0095] Comparative Example 4:
[0096] This comparative example is a positive electrode material coated with magnesium phosphate and multi-walled carbon nanotubes. The mass content of magnesium phosphate is 0.3wt% relative to the positive electrode material, and the preparation method is as follows:
[0097] (1) 0.3 wt% Mg2(PO4)3 was uniformly dispersed in a 5 wt% multi-walled carbon nanotube solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 minutes to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is ethylene glycol, which contains 0.2 wt% LDS, and the average length of the multi-walled carbon nanotubes is 5 μm and the average outer diameter is 12 nm.
[0098] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@Mg2(PO4)3.
[0099] Comparative Example 5:
[0100] This comparative example is a positive electrode material coated with lanthanum phosphate and sucrose. The mass content of lanthanum phosphate is 0.3wt% relative to the positive electrode material, and the preparation method is as follows:
[0101] (1) 0.3 wt% LaPO4 was uniformly dispersed in a 5 wt% sucrose solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 min to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the sucrose solution was ethylene glycol containing 0.2 wt% LDS.
[0102] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#C@LaPO4.
[0103] Comparative Example 6:
[0104] This comparative example is a positive electrode material coated with lanthanum phosphate and multi-walled carbon nanotubes. The mass content of lanthanum phosphate is 0.3wt% relative to the positive electrode material. The preparation method is as follows:
[0105] (1) 0.3 wt% LaPO4 was uniformly dispersed in a 5 wt% multi-walled carbon nanotube solution, and then 5 g of nickel-iron-manganese-based positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 is dispersed in the modified solution and stirred at 400 rpm and 110°C for 60 minutes to vaporize the solvent and obtain a positive electrode composite material precursor powder, wherein the solvent in the multi-walled carbon nanotube solution is deionized water containing 0.2 wt% LDS, and the average length of the multi-walled carbon nanotubes is 5 μm and the average outer diameter is 12 nm.
[0106] (2) The precursor powder obtained in step (1) is pressed into a disc with a diameter of 14 mm and a thickness of 1 mm in a tablet pressing mold at a pressure of 10 MPa, and then the disc is placed in a box furnace in an oxygen atmosphere, and the temperature is raised to 650° C. at a heating rate of 3° C. / min, kept for 10 h, and then naturally cooled to room temperature; the sintered sample is taken out and crushed, and then passed through a 300-mesh sieve to obtain a sodium ion battery positive electrode composite material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#CNT@LaPO4.
[0107] The positive electrode materials of each embodiment and comparative example were assembled into button batteries, and constant current charge and discharge tests and cycle tests were performed on the assembled button batteries. The capacity and cycle performance effect data are shown in Table 1, wherein the test voltage range is 2.0-4.2V, the test temperature is 25°C, and the test ratio is 1.0C.
[0108] Table 1 Capacity and cycle performance of each embodiment
[0109]
[0110]
[0111] Table 2 Capacity and cycle performance of each comparative example
[0112]
[0113] From the half-cell test results of each embodiment in Table 1, it can be seen that after coating the layered positive electrode material, the first cycle discharge specific capacity of the sodium battery remains basically unchanged or even increases slightly, which may be due to the high-valent metal promoting the high-voltage redox reaction. In addition, the coating generally significantly improves the capacity retention rate after 100 cycles. It is worth noting that the content of the coated oxide needs to be appropriate, and the burn-back temperature and time also need to be reasonably selected, otherwise it will affect the electrochemical performance. The use of different elements for coating treatment has a significant effect on improving the long-cycle performance of the layered positive electrode material.
[0114] The long cycle test at 1C rate was carried out on Example 1, Examples 7-9, and Comparative Examples 1-6. The results are shown in Figure 4 , Figure 5As shown, the results show that compared with Comparative Example 1, the discharge specific capacity and cyclability of the positive electrode material in Example 1 have been significantly improved, while the capacity of Comparative Example 2 remains unchanged after soaking after being coated with multi-walled carbon nanotubes, and the retention rate is improved, indicating that the secondary sintering of coated conductive carbon can avoid damage to the material by the incident process; although the capacity of Comparative Example 3 decreases after soaking, the retention rate is significantly improved and the capacity after two hundred cycles is still higher than that of Comparative Example 1, which shows the excellence of the positive electrode material coated with high-valent metal phosphate. In addition, compared with the low-valent magnesium element selected in Comparative Example 4, the high-valent metal obviously has a better modification effect, while the sucrose selected in Comparative Example 5 has poor reducibility and cannot be complexed with metal ions, and the capacity also decreases after soaking in the solution. Example 7 selects citric acid, which can be complexed with ions in the solution and has a certain reducibility, so the carbon coating effect is improved, and ascorbic acid with a similar mechanism of action also has a similar effect. In addition, the effect of high-valent metal phosphates with a higher mass fraction has also decreased, which may be due to the performance degradation caused by the excessively thick coating layer affecting the diffusion of sodium ions on the surface. The deionized water solution selected in Comparative Example 6 has a strong corrosive effect on the O3 positive electrode material, resulting in a serious reduction in capacity.
[0115] The SEM images of Example 1, Comparative Example 1 and Comparative Example 3 are shown as follows: Figure 1 , Figure 2 and Figure 3 As shown, the presence of coated particles can be clearly observed on the surface of the particles of Example 1, the surface of the particles of Comparative Example 1 is relatively smooth, and the surface of Comparative Example 3 is covered with dense wrinkles, which is due to the generation of more residual alkali after immersion in the solution. Figure 5 This is a TEM image of the positive electrode composite material prepared in Example 1. It can be seen that the bulk phase of Example 1 presents highly crystalline O3 phase lattice stripes, while the surface is an amorphous coating layer with a thickness of 1-4 nm.
[0116] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
[0117] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A positive electrode composite material, characterized in that: The positive electrode composite material comprises a positive electrode material matrix and a coating layer coated on the surface of the positive electrode material matrix, wherein the coating layer is composed of mixed phosphate and carbon source.
2. The positive electrode composite material according to claim 1, characterized in that: The mixed phosphate is M x PO4, M x One or more of P2O7, HPO3, H3PO4, NH4H2PO4, wherein M includes one or two of Sb, Sc, Y, La, Ce, Sm, Gd, Dy, and Ta; and the carbon source is one or two of glucose, citric acid, ascorbic acid, carbon nanotubes, and graphene.
3. The positive electrode composite material according to claim 1, characterized in that: The chemical formula of the positive electrode composite material is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2#MPO4@C, wherein M includes at least one of Sb, Sc, Y, La, Ce, Sm, Gd, Dy, and Ta; and C is one or two of glucose, citric acid, ascorbic acid, carbon nanotubes, and graphene.
4. The positive electrode composite material according to claim 1, characterized in that: In the coating layer, the mass of the carbon source accounts for 1-10wt% of the mass of the positive electrode material matrix, and the mass of the mixed phosphate accounts for 0.3-3wt% of the mass of the positive electrode material matrix; the thickness of the coating layer is 1-15nm.
5. A method for preparing the positive electrode composite material according to any one of claims 1 to 4, characterized in that: include: The cathode material matrix is added into the modified solution of the mixed phosphate and the carbon source to be evenly dispersed, stirred and heated to vaporize the solvent, and dried to obtain a cathode material precursor powder of the mixed coating layer; The mixed coating layer positive electrode material precursor powder is tableted and sintered to obtain a positive electrode composite material.
6. The method for preparing the positive electrode composite material according to claim 5, characterized in that: The modified solution of mixed phosphate and carbon source comprises phosphate, carbon source, dispersant and organic solvent; Wherein, the dispersant includes one or more of polyethylene, polypropylene, polystyrene, sodium polyacrylate, and polyvinyl alcohol; and the organic solvent includes one or more of ethanol, ethylene glycol, ethyl ether, and isopropyl ketone.
7. The method for preparing the positive electrode composite material according to claim 6, characterized in that: In the modified solution of the mixed phosphate and carbon source, the mass fraction of the phosphate is 0.3-3wt%, the mass fraction of the carbon source is 1-10wt%, and the mass fraction of the dispersant is 0.1-0.3wt%.
8. The method for preparing the positive electrode composite material according to claim 5, characterized in that: The steps of adding the cathode material matrix to the modified solution of the mixed phosphate and the carbon source to disperse uniformly, stirring and heating to vaporize the solvent, and drying to obtain the mixed coating layer cathode material precursor powder include: The cathode material matrix is added to the modified solution of mixed phosphate and carbon source and dispersed evenly, stirred at 80-110°C to vaporize the solvent, and then dried at 80-120°C for 6-10h to obtain a mixed coating layer cathode material precursor powder.
9. The method for preparing the positive electrode composite material according to claim 5, characterized in that: The step of tableting the mixed coating layer positive electrode material precursor powder and sintering it to obtain a positive electrode composite material comprises: The mixed coating layer positive electrode material precursor powder is tableted, placed in an inert gas or oxygen atmosphere, heated to 450-850° C. at a heating rate of 2-5° C. / min, and kept warm for 5-12 hours to obtain a positive electrode composite material.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode composite material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for modifying phosphate-coated lithium-rich manganese-based cathode material
CN109713260A
Graphene tightly coated SiO negative electrode material and preparation method thereof
CN109742363A
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN117239102A
Sodium-ion battery positive electrode material and preparation method thereof
CN117254000A
Method for preparing graphene-coated powder material, and product of method
WO2018049844A1